ASSESSMENT OF PROMISING LOCAL WALNUT FORMS FOR THE SOUTH AND SOUTH-EAST OF KAZAKHSTAN - Oleychenko Sergey Nikolaevich,; Yegizbayeva Togzhan Kadylbekovna,; Apushev Amangeldy Kairbekovich,; Nusipzhanov Nurdan Sebegatovich, (Academic Journal of Physical and Chemical Sciences, 2020)
Currently, Kazakhstan has increased interest in nut crops, especially walnuts, which bring stable yields in the most favorable areas for it. Walnut is a valuable product, and its industrial cultivation in the southern regions of the Republic has a certain perspective. Biometric observations, accounting for productivity and average weight of the fetus and nucleus, and phenological observations were carried out. The General condition of plants was also assessed. Selected and studied 3 forms established during the period of expedition research in the Almaty region and two in Turkestan. Observations of promising forms of walnuts in two regions have shown that the previously selected forms show a fairly high adaptive stability and yield stable yields of high enough quality. It should also be noted that the fruiting of 2018 Almaty forms took place after winter drops to -33C and 10 days of steady cooling at the level of 23-28C. This allows us to include all three promising forms, Aliyar (Issyk), Enbekshikazakh district, Krivenok from Kyrgyzaulda and from the Seidaliev estate, Karasay district. The largest of them is Aliyar, with an average weight of more than 13 g, a core yield of 51%, and not very strong shell. The seidali form is the least large-fruited and does not meet the requirements for the size of the fruit. The form of Kyrgyzaulda also does not reach 11 g, but it has almost a paper shell and an excellent taste of the core, which can even be attributed to dessert. The unique properties of the Turbat nut from the 19th century continue to surprise. No frost damage and saving in more. more than 100 years of age of physiological activity. This year's yield was higher, while maintaining the size of nuts with an average weight of 13 g. Further work is planned to introduce it to culture in vitro for micro-propagation and prepare documentation for recognition as a breeding achievement of global significance.